The Effect of Company Size on the Implementation of Fixed Assets Depreciation Method - Rosalinda Agustin (Journal of Contemporary Information Technology, Management, and Accounting, 2021)
This study aims to determine the effect of company size on the determination of the depreciation method of fixed assets. The research problem is as follows: Does company size affect the choice of depreciation method. The purpose of this study is to determine the effect of company size on the choice of depreciation method for fixed assets. This study uses secondary data obtained from the Indonesia Stock Exchange, namely companies that are members of the LQ45 company in 2019. The data analysis methods used are descriptive statistics, classical assumption tests, and hypothesis testing consisting of Simple Linear Regression Methods, Coefficient of Determination, and T test. The results of this study are the effect of company size on the depreciation method of fixed assets shows an insignificant relationship, this proves that company size does not have an influence in determining the method of depreciation of fixed assets.